Understanding tumor localization in multiparametric MRI of the prostate—effectiveness of 3D printed models - Haack, Maximilian; Reisen, Katja; Ghazy, Ahmed; Stroh, Kristina; Frey, Lisa; Sparwasser, Peter; Duwe, Gregor; Mager, Rene; Haferkamp, Axel; Borgmann, Hendrik (Frontiers in Surgery, 2023)
Introduction: Understanding tumor localization in multiparametric MRI (mpMRI) of the prostate is challenging for urologists but of great importance in mpMRI-fused prostate biopsy or radical prostatectomy. The aim was to evaluate the effectiveness of 3D printed models of the prostate to help urologists to locate tumors. Methods and Participants: 20 urologists from University Medical Center Mainz (Germany) were asked to plot the location of a cancer suspicious lesion (PI-RADS≥4) on a total of 30 mpMRI on a prostate sector diagram. The following 3 groups (as matched triplets) were divided into: mpMRI only, mpMRI with radiological report and mpMRI with 3D printed model (scaled 1:1). Statistical analysis was performed using one-way and two-way ANOVA (with bonferroni post-test).Results: Overall, localization of the suspicious lesion was superior with the radiological report